2017
DOI: 10.1186/s12885-016-3017-3
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and roles of combining temozolomide with whole brain radiotherapy in protection neurocognitive function and improvement quality of life of non-small-cell lung cancer patients with brain metastases

Abstract: BackgroundBrain metastasis (BM) is a poor prognostic factor for non-small-cell lung cancer (NSCLC). The efficacy and roles of combining temozolomide (TMZ) with whole brain radiotherapy (WBRT) in protection neurocognitive function (NCF) and improvement quality of life (QOL) were investigated and compared with WBRT alone in the treatment of NSCLC patients with BM.MethodsA total of 238 NSCLC patients with BM were reviewed and categorized into WBRT plus TMZ (RCT) arm and WBRT alone (RT), respectively. The efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Neurocognitive dysfunction has been identified after whole-brain radiation and chemotherapy. 8 , 9 However, our patient only experienced a slight decrease in recent memory, comprehension, and occasionally a slight decrease in hearing ability, which did not affect his normal daily life.…”
Section: Casementioning
confidence: 60%
See 1 more Smart Citation
“…Neurocognitive dysfunction has been identified after whole-brain radiation and chemotherapy. 8 , 9 However, our patient only experienced a slight decrease in recent memory, comprehension, and occasionally a slight decrease in hearing ability, which did not affect his normal daily life.…”
Section: Casementioning
confidence: 60%
“… 7 A subgroup analysis showed that the treatment of NSCLC patients with whole-brain radiation therapy (WBRT) combined with TMZ had a significantly superior objective response rate (ORR; RR =1.38) to that of WBRT alone (RR =1.34, P <0.00001). 8 WBRT is one of the therapeutic options for LM. Although it may damage neurocognitive functions, 9 it is the preferred option, especially for patients with symptomatic multiple brain metastases.…”
Section: Introductionmentioning
confidence: 99%
“…In another trial, the addition of TMZ to RT conferred an advantage in terms of PFS and OR (P<0.05), but there was no significant improvement in OS compared with RT alone. There was little difference in QoL between the two groups (20). A trial reported that the OR rate of concomitant WBRT with TMZ was 45%.…”
Section: Discussionmentioning
confidence: 95%
“…They documented that RT plus TMZ arm was associated with signi cantly more grade 3 to 4 nausea and thrombocytopenia. [17] Yong et al [20] and Deng et al [21] concluded that though TMZ in combination with WBRT is associated with higher incidence of adverse events particularly nausea and thrombocytopenia but patients can tolerate these effects and can be managed using medications.…”
Section: Discussionmentioning
confidence: 99%